Pengembangan Aplikasi Manajemen Pelatihan Laboratorium Software Engineering Di Fakultas Teknik Sistem Komputer - Faiz Risaludin Islami; Kodrat Iman Satoto; Rinta Kridalukmana (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2016)
System computer engineering of Diponegoro University has a software engineering laboratory fonctioned to provide the learning and training activities in order to give the opportunity for the students, to examine and to apply the theory or the research and the verification scientifical subject study or a part of certain subject study. The probleme emerge in this training is less the information about the training accepted by the society who willing to attend the training at the software engineering laboratory. In propose, to solve all the problemes appear, the writer make a Management Trainee Developement Application System of Software Engineering Laboratory at Faculty of System Computer Engineering gave a complete information about the training and the registration in software engineering laboratory. Management Trainee Application of Software Engineering Laboratory at Faculty of System Computer Engineering is an application based on website, made by using the program language PHP in scope Framework Code Igniter, and also MySQL for database. The developement methode used the waterfall methode, while designing the application used the UML modele. The result from this application is the realization an application based on website which is abble to manage the trainee data in software engineering laboratory, for example to manage the participant training data, the list of training data, the time schedule training data, admin data, the participant traininh data along the completed training History data.